They Who do not Grieve - Figiel, Sia (Chatto & Windus, 2000)
Weaving together the stories of three generations of Samoan women, contrasting the traditional and the modern,They Who Do Not Grieveis a stunning new novel from one of the Pacific's most exciting writers. Malu, brought up by her grandmother, has only a ghostly memory of her dead mother. And 'malu' is also the name of the Samoan woman's traditional tattoo, and the shame and grief not completing the tattoo ceremony can haunt a life forever. Young Malu, watching the Americans living on the island, sees the modern way, the Nineties discontent overtaking the Sixties notions of an island paradise, whilst hearing tales from the older Samoan women of the old life. Although destined to repeat the patterns of the past, Malu can turn them into vivid stories for the future.
Keywords: Samoan Island; Juvenile Fiction